Implementasi Sistem Monitoring Daya Listrik Berbasis Web dan Protokol Komunikasi Websocket - Zakky Ramadhan; Sabriansyah Rizqika Akbar; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Electricity usage and its price are always increased every year which encourages people to control their electricity usage. We can control electricity usage by doing electricity usage monitoring. In this study, we developed an electric power monitoring system which installed on the power strip using current transformer sensor YHDC SCT-013-000 and NodeMCU microcontroller. So, electric power usage of electronic devices that plugged into the power strip will be monitored. For data transmission, we used Websocket protocol for communicating all monitoring devices to the server. All monitoring data is saved to database server and electricity monitoring output will be showed using web interface. We hope users can monitor their electricity usage easier and more accurate. Based on the test, we get up to 97,14% accuracy result for electric current, up to 99% for electric voltage, and up to 98% accuracy result for electric power calculation. We also get a good performance with an average of 160,8 milliseconds for data monitoring acquisition. For the monitoring web, we built a web which has features such as showing electric power usage and estimated power cost on each monitoring devices.